Scenario the Use of Free Software in Geographic Information Systems (GIS) in Brazil - Milaré, Gisele; Silva, Normandes Matos da; Paranhos Filho, Antonio Conceição (Anuário do Instituto de Geociências, 2016)
This study aims to present an overview of the free software use in geographic information systems (GIS ) in Brazil, defining trends and the thematic areas that are most used. For this, through scientometrics, articles published in the Brazilian Symposium on Remote Sensing were analyzed. This event has been chosen because it has been accomplished since 1978, represent the most important congress in Brazil and thus reflects the trends and uses of geotechnologies in the country. There was the analytical work between 1978 and 2013, totaling 6.778 items. Of these, 2.128 articles have cited the use of free software. There was an increasing trend , from 90's , averaging 32 % of published articles using free software over the past 25 years. Environmental analysis was the most constant theme in the manuscripts published which used free software in GIS, with 519 articles.